Towards interoperability in P2Pworld: An indexing middleware for multi-protocol peer-to-peer data sharing - Rezende, Evandro S. [UNESP]; Dodonov, Evgueni [UNESP]; Ulson, Roberta S. [UNESP]; Cavenaghi, Marcos A. [UNESP]; Lobato, Renata S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Despite the abundant availability of protocols and application for peer-to-peer file sharing, several drawbacks are still present in the field. Among most notable drawbacks is the lack of a simple and interoperable way to share information among independent peer-to-peer networks. Another drawback is the requirement that the shared content can be accessed only by a limited number of compatible applications, making impossible their access to others applications and system. In this work we present a new approach for peer-to-peer data indexing, focused on organization and retrieval of metadata which describes the shared content. This approach results in a common and interoperable infrastructure, which provides a transparent access to data shared on multiple data sharing networks via a simple API. The proposed approach is evaluated using a case study, implemented as a cross-platform extension to Mozilla Firefox browser, and demonstrates the advantages of such interoperability over conventional distributed data access strategies. © 2009 IEEE.
Keywords: Cross-platform; Distributed data access; Firefox; Mozilla; Multiple data; Multiprotocols; New approaches; Peer to peer; Peer-to-peer data-sharing; Peer-to-peer file sharing; Peer-to-Peer networks; Transparent access; Indexing (of information); Internet; Internet protocols; Interoperability; Metadata; Middleware; Web browsers; World Wide Web; Distributed computer systems